MARCAJE DE CAMPONOTUS MOROSUS SMITH , 1858 (HYMENOPTERA : FORMICIDAE ) SEGUN LA TECNICA DE FRESNEAU Y CHARPIN - Ipinza-Regla, Joaquín; Martínez, Jorge; Solorza, Jaime (Acta Entomológica Chilena, 2022)
To study ihe división of laboui in ants of the genus Caniponotus, a method of individual marking by pholography was developed following Fresnau and Charpin recommendations. Using these marks it is possiblc to check and control the activitics of individual ants.